Aislamiento y caracterización de microorganismos ácido-lácticos con potencial probiótico a partir de leche de manatí antillano (Trichechus manatus) (2021)
The West Indian manatee (Trichechus manatus) is an endangered species due to the hunting of its individuals and the destruction of its ecosystem. Hence different programs and investigations have been developed seeking for the conservation of the species. This work evaluated the microbiological composition of manatee milk through classical microbiologicaly methods, in order to isolate and identify strains with probiotic potential that could complement the diet of baby manatees in rehabilitation processes for their subsequent reintroduction into the natural environment. A total of 111 different bacterial and yeast morphotypes were isolated from four manatee milk samples. 84 of these corresponded to Gram positive bacteria and 18 to Gram negative ones. The remaining 9 isolates presented a yeast morphology. 52 bacterial strains were identified using 16S ribosomal RNA gene sequencing. The predominant families are Staphylococcaceae and Erwiniaceae, among the Gram positive and Gram negative, respectively. Among the recovered species and genera...